Linguistic interference in El Zorro de Arriba y el Zorro de Abajo by José María Arguedas - Aquino Palacios, Ingrid Maritza (2021)
The objective of the research was to analyze the linguistic interferences in the literary work El Zorro de Arriba y el Zorro de abajo by José María Arguedas, one of the most emblematic works of the author, the problem was: What are the linguistic interferences of the literary work The Zorro Above and the Fox Below by José María Arguedas Altamirano? The research is of the substantive-descriptive type, with a simple descriptive design. The method used was descriptive and during the research process observation was used to detect linguistic interference. The main conclusion was: The main linguistic interferences that exist in the literary work El Zorro de Arriba y el Zorro de Abajo by José María Arguedas are: phonetic-phonological, morphological, syntactic and with the presence of foreignness and semantic.